Rapunzel syndrome – A rare form of trichobezoar: A case report - L., Thayumanavan; K., Rajkumar; M., Kennan (Journal of Digestive Endoscopy, 2013)
Hair ball in the GI tract is called trichobezoar and the Rapunzel syndrome is a very rare form of trichobezoar found in patients with psychiatric illness in whom the ingested hair extends from the stomach into the small intestine. Trichotillomania (hair pulling) and trichophagia (chewing of hair) are intrinsic to the development of Rapunzel syndrome. A small number of patients have been reported in whom the gastric trichobezoar has a long tail and extends throughout the small bowel to the cecum. This condition, known as the Rapunzel syndrome, occurs almost exclusively in young girls. We report a case Rapunzel syndrome who presented with history of upper GI obstruction and weight loss. Upper GI endoscopy revealed a large trichobezoar occupying fundus of stomach extending along the whole stomach into duodenum beyond its 3rd part. It was treated successfully with surgery followed by psychiatric consultation. We will review the literature on the subject as well. (J Dig Endosc 2013;4(1):19–21)
Keywords: Trichobezoar; Trichillotomania; Trichophagia; Psychiatric disorder; Upper GI obstruction; Surgery